2018
DOI: 10.1002/pi.5630
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, mechanical properties and electromagnetic shielding effectiveness of poly(styrene‐b‐ethylene‐ran‐butylene‐b‐styrene)/carbon nanotube nanocomposites: effects of maleic anhydride, carbon nanotube loading and processing method

Abstract: Nanocomposites based on poly(styrene-b-ethylene-ran-butylene-b-styrene) (SEBS) and carbon nanotubes (CNTs) (SEBS/CNT)as well as SEBS grafted with maleic anhydride (SEBS-MA)/CNT were successfully prepared for electromagnetic shielding applications. Both SEBS/CNT and SEBS-MA/CNT nanocomposites were prepared by melt compounding and were post-processed using two different techniques: tape extrusion and compression moulding. The different nanocomposites were characterized by Raman spectroscopy and rheological analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In addition, the EMI SE of TPU/CB-PPy is quite similar to that presented by Ramoa et al (2013) for TPU/CB composites. Furthermore, the EMI SE values found for TPU/CNT composites containing 3 to 8 wt% of filler are similar or quite higher than those results observed in composites containing different carbonaceous fillers (Al-Saleh et al, 2013;Jeddi and Katbab, 2017;Kumar et al, 2017;Kuester et al, 2018). According to the literature (Li et al, 2006), the desirable EMI SE is at least−20 dB for commercial application, which corresponds to 99% of radiation attenuation (Chen Z. et al, 2013;Ramoa et al, 2013).…”
Section: Figure 5 | Total Emi Se Se a And Se R Values Of Composites supporting
confidence: 67%
See 1 more Smart Citation
“…In addition, the EMI SE of TPU/CB-PPy is quite similar to that presented by Ramoa et al (2013) for TPU/CB composites. Furthermore, the EMI SE values found for TPU/CNT composites containing 3 to 8 wt% of filler are similar or quite higher than those results observed in composites containing different carbonaceous fillers (Al-Saleh et al, 2013;Jeddi and Katbab, 2017;Kumar et al, 2017;Kuester et al, 2018). According to the literature (Li et al, 2006), the desirable EMI SE is at least−20 dB for commercial application, which corresponds to 99% of radiation attenuation (Chen Z. et al, 2013;Ramoa et al, 2013).…”
Section: Figure 5 | Total Emi Se Se a And Se R Values Of Composites supporting
confidence: 67%
“…Several interesting works concerning the production of EMI shielding polymer composites with improved electrical conductivity and EMI SE values have been reported (Yavuz et al, 2005;Mahapatra et al, 2008;Sudha et al, 2009;Kim et al, 2011;Kaur et al, 2012;Zhang et al, 2012;Al-Saleh et al, 2013;Sharma et al, 2016;Kumar et al, 2017;Kuester et al, 2018;Kumar and Patro, 2018). The most commonly used conductive fillers are carbon fillers, such as carbon nanotubes (CNT) (Mahapatra et al, 2008;Socher et al, 2011;Kaur et al, 2012;Zhang et al, 2012;Al-Saleh et al, 2013;Kumar et al, 2017;Yu et al, 2018), expanded graphite (EG) (Piana and Pionteck, 2013;Kuester et al, 2016), carbon black (CB) (Sumfleth et al, 2009;Chen J. et al, 2013;Burmistrov et al, 2016;Pan et al, 2016;Jeddi and Katbab, 2017;Mondal et al, 2018), graphene (GE) (Al-Saleh, 2015;Sharma et al, 2016) and graphene nanoplateles (GnP) (Chu et al, 2012;Al-Saleh, 2016), and intrinsically conducting polymers (ICP), for instance, polypyrrole (PPy) (Yavuz et al, 2005;Taunk et al, 2008) and polyaniline (PAni) (Sudha et al, 2009;Kim et al, 2011;Oyharçabal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al 5 obtained CNT/polyvinylidene fluoride (PVDF) composites with 4 wt % CNT exhibiting a SE of 36.8 dB. Demarquette et al 6 found that the poly(styrene-b-ethylene-ran-butylene-b-styrene) (SEBS)/CNT nanocomposite containing 8 wt % CNT contents obtained by compressive molding showed a SE of 56.73 dB. However, the mechanical properties of shielding materials are easily scarified due to the high loading of fillers in order to obtain a high SE value, which restricts their wider application.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electrically conductive and semi-conductive polymer composites are being more and more involved in a wide range of industrial applications including flexible electronics, soft robotics, health monitoring devices, anti-static materials, sensors, protective screens for power cables, electric field-grading materials for cable accessories and electromagnetic interference shielding materials [1][2][3][4][5][6][7][8][9][10]. Different conductive particles have been investigated as fillers for these composites such as metallic particles and carbon based particles including carbon fibers, carbon black, carbon nanotubes, reduced graphene oxide, exfoliated graphite and graphene [3][4][5][11][12][13][14][15][16]. In particular, graphene gained increasing interest recently, to be used as an effective filler in polymer composites to enhance their electrical, thermal and mechanical properties, due to its outstanding intrinsic properties, low density and very attractive geometry, i.e., high aspect ratio, high effective surface area and plate-like geometry [10,12,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%